Scientific Opinion on the safety and efficacy of Pediococcus acidilactici (CNCM I‐3237, CNCM MA 18/5M‐DSM 11673) and Pediococcus pentosaceus (DSM 23376, NCIMB 12455, NCIMB 30237 and NCIMB 30168) as silage additives for all species - EFSA Panel on Additives and Products or Substances used in Animal Feed (FEEDAP) (EFSA Journal)
Abstract Two strains of Pediococcus acidilactici and four strains of P. pentosaceous are each intended to improve ensiling at proposed doses ranging from 1.4 × 107 to 1.0 × 108 colony‐forming units (CFUs)/kg fresh material. Both bacterial species are considered by EFSA to be suitable for the Qualified Presumption of Safety approach to safety assessment. As the identity of all strains was clearly established and as no antibiotic resistance of concern was detected, the use of these strains in silage production is presumed safe for livestock species, consumers of products from animals and the environment. The material safety data sheet proposed indicates that preparations containing the strains maycause irritation on contactwith skin oreyes. In addition, given the dusting potential and proteinaceous nature of the active agents, the Panel considers it prudent to treat all six additives as skin and respiratory sensitisers. Studies with laboratory‐scale silos are described for each strain, each lasting at least 90 days, made using forage samples representing materials that are easy to ensile, moderately difficult to ensile and difficult to ensile. One strain of P. acidilactici and three strains of P. pentosaceus were shown to have the potential to improve the production of silage from forage species that were easy, moderately difficult and difficult to ensile by reducing the pH and increasing the preservation of dry matter and/or protein, when used at the doses proposed. Another strain of P. pentosaceus appeared to favourably affect the ensiling process by reducing the pH, but only when used in combination with a specific strain of Lactobacillus plantarum. However, the consequences of a more rapid reduction in pH for the preservation of nutrients were not shown. Data for the remaining strain of P. acidilactici were partly contradictory and inconsistent and no conclusions on efficacy could be drawn.